Evaluation Indicators for Citations and References in Master’s Thesis in Education: A Peruvian Sample - Hernández, Ronald M. (2019)
This research work is aimed at determining the quality of citations and references of the Master’s thesis in Education of peruvian colleges. The documental analysis  technique was used and the “Observation Guide” proposed by Martín and Lafuente (2017) was employed as an instrument, which is composed of five quality indicators for the bibliographic review (exhaustiveness, critical use of the bibliography, quality, relevance and review of previous research works); and of 9 for bibliographic references (update, number of references, self-citation, language, typology, support, complete references, accuracy and fulfillment of a standard or style). In addition, 562 bibliographic references and 1209 citations extracted from 14 theses, digitalized and published in the National Digital Repository of Peru during 2017, were analyzed. The mechanisms for citations as well as the bibliographic references were evaluated. After the descriptive-statistical analysis, it could be identified that the level achieved for both variables was “Enough”.